The relationship between trunk rotation and shot speed when performing ice hockey wrist shots - Robbins, S. M.; Renaud, P. J.; MacInnis, N.; Pearsall, D. J. (Journal of Sports Sciences, 2021)
There has been minimal work examining kinematics of ice hockey wrist shots. The objective was to determine if puck and blade speed were related to trunk rotation during wrist shots in elite and recreational players. Elite (n = 10) and recreational (n = 10) ice hockey players completed wrist shots while skating and from a stationary position on real ice. A 14 camera motion capture system collected kinematic data for the trunk, pelvis, stick, and puck. Dependent variables included peak puck and blade speeds. Independent variables included peak trunk rotation angles, trunk rotation range of motion (ROM), and group (elite vs. recreational). Hierarchical linear models compared relationships between dependent and independent variables for both skating and stationary wrist shots. Greater peak trunk rotation away from the net was related (p < 0.05) to faster puck and blade speeds for skating and stationary wrist shots. This relationship was stronger in the recreational group for skating wrist shots (p < 0.01). Greater trunk rotation ROM was related (p = 0.01) to faster puck and blade speeds for the skating wrist shots only. Coaches should encourage players to increase trunk rotation away from the net during wrist shots, especially in recreational players.